Hydrocele of canal of Nuck in an adult female: a case report - Parikh, Atish K.; Bakhshi, Girish D.; Gadekar, Deepak B.; Rahul, Kushagra; Garg, Kritika (International Surgery Journal, 2019)
A hydrocele of canal of Nuck is a rare condition seen in females, commonly in the pediatric age group. The canal of Nuck is an extension of peritoneum into the inguinal canal through the deep ring, analogous to the processus vaginalis in males. Incomplete proximal obliteration and collection of serous fluid in the sac leads to the formation of a hydrocele of canal of Nuck. Here we present a rare case of hydrocele of canal of Nuck in an adult female.